The Resurrection of Christ as the Hope for Humanity: a Socio-rhetorical Interpretation of/in 1 Corinthians 15:1-34 - Alroy Mascrenghe, M. (University of jaffna, 2018)
In a world without hope Christ gives hope through his gospel. If Christian faith looks at the things Christ has done in the past; hope looks to what God will do in the future. The main anti hope factor is death – death takes away the hope we have for the future and makes us hopeless. What good is it after all, even after believing in God for the future, we still die like all the animals of the earth? The remedy that the Bible gives centres on the resurrection of the dead. And the main assurance we have for our resurrection of Christ. In Corinthians 15 Paul look at the resurrection of Christ as the remedy to death. Resurrection lies at the heart of the Christian message regarding Christ and Christian salvation. Nowhere is this clearer than in 1 Corinthians 15 which is by far the most detailed discourse on the nature and significance of the resurrection in the entire canonical New Testament. As with so much of Paul’s theological thought, he dose not discuss the resurrection for its own sake, but because belief in the resurrection appears to have become a key issue among some of his converts in the Roman city of Corinth. The Corinthians, at least some of them did not believe in the resurrection of the dead. In 1 Corinthians 15, Paul uses a complex array of arguments to convince the Corinthians that the resurrection of the dead is indeed a reality. While these arguments in 1 Corinthians 15 have been studied from different, in this paper I will use Socio-rhetorical interpretation to analyze the text and to show that Paul’s arguments are Christo centric.
Keywords: Resurrection; Hope; Death; Biblical; Hopeless